The radiative flow of the thin-film Maxwell hybrid nanofluids on an inclined plane in a porous space - Gul, Taza; Mukhtar, Safyan; Alghamdi, Wajdi; Tag Eldin, Elsayed; Yassen, Mansour F.; Guedri, Kamel (Frontiers in Energy Research, 2022)
Maxwell fluid and stretching sheets have multiple usages in many industries. The vision of this study is to determine the properties of thin-film Maxwell Hybrid Nano-fluid on an inclined stretching sheet. Magnesium oxide (MgO) and Titanium Dioxide (TiO2) are used as nanocomponents. Maxwell fluid is utilized as a base fluid in the preparation of Nano-fluid by blending Nano components into the base fluid. The proposed flow model is solved analytically. In this article, we also consider Brownian motion and thermophoresis, and their effects that are studied simultaneously via the Buongiorno model. This study also examines the boundary layer of velocity, thermal, and concentration profiles. The proposed model of PDEs is converted into highly nonlinear ODEs by means of similarity transformation. The numerical results of liquid film motion, thermal profile, and concentration field are also shown with the help of their respective graphs based on the collected data. The solution of the model involves key parameters such as thermophoretic parameter; temperature profile, magnetic parameter, and Brownian motion are also analyzed. Magnetic parameter M, Prandtl number Pr, thickness parameter β, unsteadiness parameter S, and Euclid number EC are also deliberated graphically.